2012
DOI: 10.1111/j.1600-0560.2011.01834.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of proliferation rate, p53 staining and perforating elastic fibers in distinguishing keratoacanthoma from hypertrophic lichen planus: a pilot study

Abstract: Proliferation index is not significantly different between KA and hypertrophic LP (p = 0.059). Expression of p53 is increased in KA over hypertrophic LP (p = 0.024). The presence of perforating elastic fibers in KA is significantly different from hypertrophic LP (p < 0.0001) and suggests that elastic Verhoeff-van Gieson staining may be of practical benefit in distinguishing KA from hypertrophic LP in difficult cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
2
14
0
1
Order By: Relevance
“…Pseudocarcinomatous hyperplasia secondary to inflammation can occasionally be difficult to differentiate from keratoacanthoma, most notably in the setting of hypertrophic LE and hypertrophic LP. In an EVG‐aided study of KA and hypertrophic LP, elastic trapping was noted in 15 of 18 and 1 of the 18 cases respectively . Our results support their findings with hematoxylin/eosin staining alone.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Pseudocarcinomatous hyperplasia secondary to inflammation can occasionally be difficult to differentiate from keratoacanthoma, most notably in the setting of hypertrophic LE and hypertrophic LP. In an EVG‐aided study of KA and hypertrophic LP, elastic trapping was noted in 15 of 18 and 1 of the 18 cases respectively . Our results support their findings with hematoxylin/eosin staining alone.…”
Section: Discussionsupporting
confidence: 88%
“…Histopathologic examination in hematoxylin/eosin‐stained sections remains the key diagnostic modality for the diagnosis of KA. The phenomenon of perforating elastic fibers, sometimes referred to as elastic fiber trapping or transepithelial elastic fiber elimination , has been mentioned by some authors as a helpful identifier in the differentiation of KA, SCC and hypertrophic lichen planus (LP) . Perforating elastic fibers have been noted above scars and in the setting of hypertrophic lupus erythematosus (LE), but the frequency of this phenomenon in those entities has not been evaluated …”
mentioning
confidence: 99%
“…Histologic features suggestive of HLP include hyperorthokeratosis, wedge-shaped hypergranulosis, and psoriasiform hyperplasia of the epidermis 5 ; lichenoid interface dermatitis with eosinophils 10 ; presence of typical features of PEH; and absence of cytologic atypia, marked solar elastosis, deep extension beyond the superficial dermis, and lymphovascular or perineural invasion 2, 3. Elastic staining to visualize the presence or absence of perforating elastic fibers may assist in distinguishing between SCC and HLP; perforating elastic fibers are rarely present in HLP but may be seen in SCC 11, 12…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the frequency of this phenomenon in SCCs is only 0-26% (p < 0.001) 69,70 Elastic fiber trapping is more prominent if severe sun damage is present. 70 Electron microscopy conducted by Ohashi et al showed that basal cells of keratoacanthomas have invaginations that gradually surround elastic fibers. 71 Normal and degraded elastic fibers are seen in keratinocytes and intercellular spaces in all the layers of keratoacanthoma, and they gradually diminish toward stratum corneum, where they get eliminated off the surface (so-called transepithelial elimination).…”
Section: Use Of Evg Staining In Neoplasmsmentioning
confidence: 98%
“…69,70 Frequency of elastic trapping in keratoacanthomas ranges from 68% to almost 100% in different studies. In contrast, the frequency of this phenomenon in SCCs is only 0-26% (p < 0.001) 69,70 Elastic fiber trapping is more prominent if severe sun damage is present. 70 Electron microscopy conducted by Ohashi et al showed that basal cells of keratoacanthomas have invaginations that gradually surround elastic fibers.…”
Section: Use Of Evg Staining In Neoplasmsmentioning
confidence: 99%